A new “elfin” butterfly species of Cissatsuma Johnson, 1992 (Lepidoptera, Lycaenidae) from northwestern Sichuan, China - Krupitsky, Anatoly V. (Zootaxa, 2018)
A new species of elfin blue, Cissatsuma berezowskii Krupitsky sp.n., is described from the northwestern Sichuan Province, China, based on two old museum specimens, a male and a female. The new species differs from the most closely related one, C. albilinea (Riley, 1932), in lack of white band of ventral wing surfaces, broadened blue area of dorsal wing surfaces in female, and morphology of the male and female genitalia. The distribution map of the new species and C. albilinea is provided.